IMPACT OF INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE - Hendra Gunawan; Rica Tartila (Pusat P2M Politeknik Negeri Batam, 2017)
Science and emerging technology in the manufacturing industry made the importance of implementing knowladge based industries, it has focused the importance of the using intellectual capital in this industry. This study aims to analyze the impact of intellectual capital on the financial performance. The empirical data were drawn from panel consisting of 51 companies manufacturing in Indonesia Stock Exchange (IDX) from 2010-2014. Various regression models were examined in order to test the hypothesis included in the proposed conceptual framework. The result showed value added intellectual capital (VAIC), value added human capital (VAHU), structural capital value added (STVA) have significant effect with four financial performance measures ROA, ROE, GR, EVA. Meanwhile, value added capital employed (VACA) have significant effect with two dependent variable ROA,ROE and no significant effect on GR, EVA. The results of the overall analysis regression only VACA which had no effect with GR and EVA.the lack of available data for the appropriate analysis be the main limitations of this study. The result of this study can explained the role and importance of intellectual capital to improve financial performance for companies and the result of this study study also can be used by shareholders and investors.